Reform by Numbers : Measurement Applied to Customs and Tax Administrations in Developing Countries - Cantens, Thomas; Ireland, Robert; Raballand, Gaël (Washington, DC: World Bank, 2012)
This paper is organized as follows. In chapter two, Samson Bilangna and Marcellin Djeuwo from the Cameroon customs administration present the history and the outcomes of the performance measurement policy launched by their administra-tion: the General Directorate of Customs signed 'performance contracts' with the frontline customs officers in 2010 and with some importers in 2011. In chapter three, Jose-Maria Munoz, an anthropologist, offers a complementary view of the introduction of figures in the Cameroon tax administration. The fourth chapter ends the book's first part, which focuses on performance measurement. Xavier Pascual from the French customs administration describes the system implemented by his administration to measure the collective performance of customs units and bureaus. In chapter five, Anne-Marie Geourjon and Bertrand Laporte, who are both economists, and Ousmane Coundoul and Massene Gadiaga, who are from the Senegalese customs administration, present the use of data mining to select imports for inspection. This project is being developed in Senegal and embodies the concept of risk analysis. Sharing the same global aim to make controls more efficient, economists Gael Raballand and Guillermo Arenas from the World Bank and anthropologist Thomas Cantens from the World Customs Organization suggest, in chapter six, using mirror statistics to detect potentially fraudulent import flows. Mirror statistics calculate the gaps of foreign trade statistics between two trading partner countries. To conclude the second part on the integration of measurement in information systems, Soyoung Yang from the Korea Customs Service (KCS), in chapter eight, offers a case study on KCS's implementation of a single window system. With respect to risk analysis, the concept of single window is widespread in the trade and customs environments, but few concrete achievements have been presented and analyzed.